WELLNES TOURISM AT MEMENING TEMPLE OF YEHTENGAH ADAT VILLAGE KELUSA VILLAGE, PAYANGAN DISTRICT, GIANYAR REGENCY - Anak Agung Gede Rai Astawa (UHN IGB Sugriwa Denpasar, 2023)
Tourism that highlights the aspects of wellness/health and cultural heritage that are noble. In Yehtengah Traditional Village, Kelusa Village, Payangan District, Gianyar Regency, Bali Province, there is a tourist attraction in the form of Pancoran Solas at the Mengening Temple. This place has a very strong mystical aura that attracts spiritual aspirants to visit this place and also attracts yoga aspirants. In this study the method used is a qualitative method. Sugiyono (2020: 9) argues that the qualitative research method is a research method based on positivism or enterpretive philosophy, used to examine the condition of natural objects, where the researcher is the key instrument, data collection techniques are carried out by triangulation. The results of the review show that Pancoran Solas at the Mengening Temple in Yehtengah Traditional Village, Kelusa Village, Payangan District, Gianyar Regency, with all its spiritual activities, is very suitable to be developed as a spiritual and wellness tourism object in Bali. Supported by a very strong mystical/supernatural aura in the Mengening Temple area of Yehtengah Traditional Village